HYBRIDISATION OF FEMALE KOI (Cyprinus rubrofuscus) AND MALE KAPIAT (Barbonymus schwanenfeldii) WITH ARTIFICIAL SPAWNING IN KAMPAR DISTRICT, RIAU - Nasita, Abian Surya; Rostika, Rita; Priowirjanto, Gatot Hari; Zidni, Irfan; Davinci, Leonardo; Kurniawan, Ronal; Karsih, Okta Rizal (Asian Journal of Aquatic Sciences, 2025)
This study aims to evaluate the potential for hybridisation between female koi (Cyprinus rubrofuscus) and male kapiat (Barbonymus schwanenfeldii) through artificial spawning. The study was conducted at Kampar Ornamental Fish, Kampar District, Riau Province. The method used was a Completely Randomized Design (CRD) with two treatments: P1 (koi × koi) as the control, and P2 (koi × kapiat) as the hybrid treatment, each with three replicates. The parameters observed included fecundity, fertilisation rate (FR), hatching rate (HR), absolute length growth, and survival rate (SR). The results showed that hybridisation produced promising performance in terms of FR (21.99%), HR (55.02%), and SR (41.6%). In conclusion, hybridisation between koi and kapiat fish has the potential to produce superior varieties, although attention must be paid to environmental factors such as temperature and pH